AKTIVITAS ANTIOKSIDATIF DAN HIPOKOLESTEROLEMIK EKSTRAK TEH HIJAU DAN TEH WANGI PADA TIKUS YANG DIBERI RANSUM KAYA ASAM LEMAK TIDAK JENUH GANDA [Antioxidative and Hipocholesterolemic Activity of Green Tea and Jasmine Green Tea Extracts in Rats Fed wi - Arif Hartoyo; Mary Astuti (Jurnal Teknologi dan Industri Pangan, 2002)
The aim of  this study was to evaluate in-vivo the antioxidative and hipocholesterolemic activity of green tea and jasmine green tea extracts in 3.5-month-old Sprague Dawley  male rats given high PUFA diet for 4 weeks.   In rats fed with (adlibidom or forcely adted)  high PUFA diet supplemented  with green tea extract, serum and liver homogenate malondialdehyde level and the liver homogenate cholesterol level were greater than rats fed with  the high PUFA diet supplemented with jasmine green tea extract pn the control.  In contrast, no change was observed in serum cholesterol level in rats fed with the high PUFA diet  containing green tea or jasmine green tea extract as compared with the high PUFA diet.